PROSES PENATAAN PESAN DIGITAL CONTENT PADA AKUN SOSIAL MEDIA (FACEBOOK & INSTAGRAM) KLINIK KECANTIKAN LALITA SIDOARJO DALAM MENJANGKAU KONSUMEN DI USIA 25 – 40 TAHUN - M. Fadeli; Tira Fitriawardhani; Muhammad Aris Oktavianto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
This research is a study of how the digital content process is formed on the social media accounts of the Lalita Sidoarjo beauty clinic in reaching consumers, considering that digital content during the digital era and especially during the COVID-19 pandemic is very much needed by an agency or company. In the world of journalism, we encounter what is called digital media, namely digital-based information and entertainment media or commonly called online. This digital content phenomenon is increasingly recognized by the general public when the emergence of content creators and causes many agencies and companies to use digital content to market or promote their interests. This study aims to determine the process of creating digital content flow and distributing it to Lalita beauty clinic consumers in order to have an impact on the clinic. By using descriptive qualitative research methods and data collection techniques for this study using participant observation and documentation. Participant observation was carried out because the researcher also took part in the activities being observed. Documentation was carried out to find out the extent to which digital content was good and could be enjoyed by lalita consumers. Keywords: Digital Content, Content Creator, Branding, Digital Media, findings